The Use of Deixis in the Students’ Writing Narrative Texts - Isma Hidayati; Sulisyaningsih Sulisyaningsih; Abd. Syakur (Budapest International Research and Critics University, 2022)
The study's goal was to identify different types of deixis and types of errors found in students' narrative text writing. There is person deixis, which is the name of the person in the story, spatial deixis, which is the location of the story, temporal deixis, which is the time when the story events, social deixis, which is the social in the surrounding environment, and discourse deixis, which is the part or the next chapter of the story (Levinson, 1983). The descriptive qualitative method was used in this study. The subjects were eight 10th grade students from SMK IKIP Gedangan in Sidoarjo. The instrument in this study was the students' work who took the remedial because their score was less than 70. Students were assigned to write Narrative texts by the teacher. The data was analyzed, examined, and a conclusion was reached based on the deixis. The researchers discovered deixis and error analysis in student writing. There are kind deixis of stories in narrative text that students written like temporal deixis, person deixis, spatial deixis, social deixis, and deixis discourse. For the error analysis there are ommission, addition, misinformation and misordering.